Model Pembentukan Budaya Religius pada Sekolah Islam Terpadu Berbasis Pembiasaan Keagamaan - Riswan, Muh; Patappa, Maghfira Maulani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explore the model of religious culture formation at SMP IT Al-Fityan School Gowa through a qualitative descriptive approach. Data were obtained from observations, interviews, and documentation, then analyzed through thematic coding with informants: the principal, vice principal for curriculum, 2 teachers, and 3 students. The research findings indicate that religious culture is institutionalized through daily practices such as greetings, dhuha prayer, Al-Qur'an recitation, and special programs such as the Weekend Tahfidz Club and MABIT. The formation process is shaped through structural, formal, mechanical, and organic approaches. Supporting factors include leadership commitment, teacher competence, parental involvement, and facilities, while inhibiting factors consist of student involvement, technology use, and external influences. This study highlights the role of school culture in promoting religious values and suggests further research on its impact on student character development.